Relationship Analysis Between Characteristics, Safety Riding Knowledge, and Intensity of Driver Mobility in Students with Traffic Accident Rates (Study Case at Senior High School 1 Blora) (International Journal of Active Learning, 2022)
By the Director General of Land Transportation in Central Java, traffic accidents that happen are dominated by drivers with high school educational backgrounds. Based on "Anatomy Report" by Blora Traffic Police, the number of accident incidents with a high school equivalent educational background is 206 out of total 313 cases. SHS 1 Blora is one of the high schools in Blora that has carried out face-to-face learning activities starting in late 2020, giving rise to probability of students mobilizing by vehicle. By Close observation found that 20% of the 80 students had accidents with one incident died, and most of them suffered severe injuries. The purpose of the study to determine whether characteristics, knowledge of safety riding, and intensity of mobility influenced the incidence rate of accidents that occurred in SHS 1 Blora, through a cross-sectional approach and quantitative analytical observational research design that used questionnaires as the main instrument. From 176 student data that were considered valid, it was concluded that age and education level as form of characteristic factors, then the level of understanding of safety riding, and the use of PPE, which is included in safety riding knowledge, have a close relationship with the level of accidents that occurs.